“ SOLO GLOBAL BUSINESS ERUDITION DI SOLOBARU ” TOWN SQUARE SEBAGAI PEMERSATU SEKOLAH BISNIS DAN RENTAL OFFICE DENGAN KONSEP HYBRID BUILDING - Muhammad Adzan Vivalditama; MDE Purnomo; Ana Hardiana (ARSITEKTURA, 2016)
Increased investment in various sectors of the economy, providing employment opportunities and entrepreneurship opportunities are greater in Solo Baru Region. Increased business activity needs to be supplemented by the provision of trade facilities, offices and education. Trading facilities and offices are highly developed in Solo Baru in 2016, but for educational facilities to support business activities in Solo Baru yet available. Solo Global Business Erudition (SOLO GLOBE) is present as a place of learning and the development of business activities in Solo Baru multi-functional as the School of Business, Rental Office and Town Square. Design issues are: how the shape and appearance of the building mass of the School of Business, Rental Office and Town Square into a single unified building SOLO GLOBE by applying the concept of building a hybrid, so that the shape and building facades can clarify the function and the privacy of each building. The method used is the method of architectural design. The results obtained are the design of a building SOLO GLOBE which retains the character and privacy between each building functions without harming each other. Keywords: Architecture, Business School, Combination, Hybrid Building, Multifunction, Town Square.